2023
DOI: 10.1038/s41598-023-34143-6
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of pumpkin seeds oil on methotrexate-induced lung toxicity

Abstract: Many chemotherapeutic drugs cause adverse pulmonary reactions leading to severe pulmonary disease. Though methotrexate (MTX) is used for the treatment of cancer and other diseases, it is highly toxic with multiple adverse effects including pulmonary toxicity. Essential oils represent an open frontier for pharmaceutical sciences due to their wide range of pharmacological properties. Pumpkin seeds oil (PSO) was used to investigate its ability to alleviate methotrexate-induced lung toxicity in rats. Lung tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…In one particular study, the ability of pumpkin seed oil (PSO) to improve methotrexate-mediated lung toxicity in rats was investigated. Lung tissue analysis showed that PSO could decrease malondialdehyde levels, enhance glutathione and nitric oxide levels, increase cholinesterase activity, and reduce tumor necrosis factor-α . Another study examined the defensive effect of pumpkin seed extract against escitalopram-mediated reproductive toxicity in male mice.…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In one particular study, the ability of pumpkin seed oil (PSO) to improve methotrexate-mediated lung toxicity in rats was investigated. Lung tissue analysis showed that PSO could decrease malondialdehyde levels, enhance glutathione and nitric oxide levels, increase cholinesterase activity, and reduce tumor necrosis factor-α . Another study examined the defensive effect of pumpkin seed extract against escitalopram-mediated reproductive toxicity in male mice.…”
Section: Toxicitymentioning
confidence: 99%
“…Lung tissue analysis showed that PSO could decrease malondialdehyde levels, enhance glutathione and nitric oxide levels, increase cholinesterase activity, and reduce tumor necrosis factor-α. 109 Another study examined the defensive effect of pumpkin seed extract against escitalopram-mediated reproductive toxicity in male mice. Reproductive toxicity was observed in mice treated with 10 or 20 mg/kg escitalopram for 30 and 60 days.…”
Section: Toxicitymentioning
confidence: 99%